Reseña de Casas Gómez, M. (dir.), Paredes Duarte, Mª J. y Varo Varo, C. (eds.) (2005). VIII Jornadas de Linguística. - Varo Varo, Carmen; Paredes Duarte, M. Jesús (Pragmalingüística, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Casas Gómez, M. (dir.), Paredes Duarte, Mª J. y Varo Varo, C. (eds.) (2005). VIII Jornadas de Linguística.